Digital Media in Language Learning: EFL Students’ Perceptions of YouTube’s Effect on Speaking Proficiency - Al-Jaro, Morshed Salim; Fadhil, Rana Abdulwahid; Sahab, Abeer Adil; Shamlan, Eitab Bin; Balaqlaf, Khawlh; Bamzab, Rawan; Bahian, Marwa; Hariz, Maysa Bin; Saif, Noof Bin (Digital Technologies Research and Applications, 2026)
This study investigates English as a Foreign Language (EFL) students’ perceptions of YouTube’s effect as a digital tool on speaking skills, with particular attention to the influence of gender and educational level. The primary objectives are to examine differences in perceptions between male and female students and across varying academic levels within the English Department at Seiyun University. A mixed-methods approach was employed, combining quantitative and qualitative data collection techniques. A questionnaire was administered to 53 students, while semi-structured interviews were conducted with a purposive sample of eight students (four male and four female) representing different educational levels. Descriptive statistics, independent samples t-tests, and one-way ANOVA were utilized to analyze the quantitative data and assess the significance of differences in perception based on gender and academic level. Findings indicate that male students generally reported more favorable perceptions of YouTube’s effect on speaking skills than their female counterparts. Moreover, students at the fourth academic level demonstrated stronger beliefs in the platform’s efficacy in enhancing their speaking proficiency compared to those in lower levels. These results underscore the importance of considering demographic and educational variables when integrating digital media tools like YouTube into language learning curricula. The study recommends that language educators and curriculum designers adopt differentiated strategies to optimize the use of YouTube in speaking skill development, tailoring approaches based on learners’ gender and academic standing.